A1.34 Telocytes in minor salivary glands of patients with primary Sjögren's syndrome: association with the extent of inflammation and ectopic lymphoneogenesis. (13th February 2015) - Alunno, A; Ibba-Manneschi, L; Bistoni, O; Rosa, I; Caterbi, S; Gerli, R; Manetti, M
Abstract : Background and objectives: It has been recently reported that telocytes, a stromal cell subset involved in immune surveillance and tissue homeostasis, are hampered in the target organs of inflammatory/autoimmune disorders. Previous studies demonstrated a marked reduction in telocytes in the skin and in other organs targeted by the fibrotic process of systemic sclerosis patients and a disappearance of telocytes was observed in intestinal wall biopsies of patients with inflammatory bowel diseases. As far as salivary glands (SGs) are concerned, to date the only study available described telocyte distribution in normal parotid glands. Since no data concerning telocytes in minor SGs (MSGs) are currently available, aim of the study was to evaluate telocyte distribution in human MSGs with normal architecture, non-specific chronic sialadenitis (NSCS) and primary Sjögren's syndrome (pSS)-focal lymphocytic sialadenitis. Methods: Twelve pSS patients and 16 sicca non-pSS subjects were enrolled and serial sections of MSGs were evaluated. Haematoxylin and eosin staining was employed to assess focus score and Tarpley biopsy score. Cellular infiltrate and lymphoid organisation were characterised by immunofluorescence with double staining for CD3 and CD20 (T/B cell segregation) and single staining for CD21 (germinal centre –(GC)-like structures). Telocytes were identified by CD34 immunohistochemistry and double immunofluorescence staining for CD34 and CD31 (CD34-positive/CD31-negative stromal cells). A double staining for CD34 and CD21 was also performed to co-localise telocytes and GC-like structures. Results: In normal-MSGs telocytes were numerous and their long cytoplasmic processes surrounded vessels and formed an almost continuous layer encircling both the excretory ducts and the secretory units. In NSCS-MSGs, despite the presence of a certain degree of inflammation, telocytes were normally represented. Conversely, telocytes were markedly reduced in pSS-MSGs compared to normal- and NSCS-MSGs. Such a decrease was associated with both worsening of glandular inflammation and progression of ectopic lymphoneogenesis. In fact, telocyte reduction was more pronounced in severe FLS infiltrates with clear T/B cell segregation compared with milder FLS infiltrates without T/B cell segregation. In addition, no telocytes could be detected around ducts surrounded by inflammatory foci displaying GC-like structures. Conclusion: Our findings suggest that telocytes may be involved in MSG homeostasis and therefore in the pathogenesis of pSS. The specific pro-inflammatory cytokine milieu of pSS-MSGs may be one of the causes of telocyte loss.